prove the following :

Asked by ashwinikumar59 | 6th Sep, 2010, 05:34: PM

Expert Answer:

given α=binomial_coefficientn2=n(n-1)2!=n(n-1)2Now binomial_coefficientα2=α(α-1)2!=α(α-1)2=12n(n-1)2n(n-1)2-1                                                        =12n(n-1)2n2-n-22                                                        = 12n(n-1)2(n-2)(n+1)2                                                         =(n+1)n(n-1)(n-2)8Now  3binomial_coefficientn+14= 3(n+1)!(n-3)!4!=(n+1)n(n-1)(n-2)8Hence proved.">

Answered by  | 7th Sep, 2010, 07:27: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.